1999
DOI: 10.1002/(sici)1099-1085(19991215)13:17<2689::aid-hyp842>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Modelling subsurface flow conditions in a salinized catchment in south-western Australia, with a view to improving management practices

Abstract: Abstract:Finite element modelling of the saturated±unsaturated surface±subsurface¯ow mechanisms operative in a small salinized catchment in south-western Australia was used to help de®ne the¯ow system and explain the causes of waterlogging and salinization there. Data available at the site from a previous study were used to obtain a ®rst approximation to the¯ow system. Altering the properties of some of the strata gave a closer calibration. It was found that the modelled saturated hydraulic conductivity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Past efforts to model subsurface lateral flow in texturecontrast soils have usually represented the impeding layer of the B2 horizons as a single uniform layer, with a single value for hydraulic conductivity (Stolte et al, 1999;Cook and Rassam, 2002;Ticehurst et al, 2003a;Ticehurst et al, 2003b). While a number of studies have simulated water movement in texture-contrast soils using either single porosity or tipping bucket models (Silberstein et al, 1999;Stolte et al, 1999;Cook and Rassam, 2002;Ticehurst et al, 2003a;Ticehurst et al, 2003b), this study has demonstrated these approaches are not suitable for simulating water and solute movement in soils that contain vertic subsoils, water repellent topsoils or soluble silica bridging such as the texture-contrast soils investigated in this study. As Silberstein et al (1999) demonstrated in the Ucarro catchment, Western Australia, inability to simulate a reduction in subsoil hydraulic conductivity resulting from seasonal swelling of texturecontrast clay subsoils resulted in inadequate simulation of seasonal perched watertables and subsurface flow.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Past efforts to model subsurface lateral flow in texturecontrast soils have usually represented the impeding layer of the B2 horizons as a single uniform layer, with a single value for hydraulic conductivity (Stolte et al, 1999;Cook and Rassam, 2002;Ticehurst et al, 2003a;Ticehurst et al, 2003b). While a number of studies have simulated water movement in texture-contrast soils using either single porosity or tipping bucket models (Silberstein et al, 1999;Stolte et al, 1999;Cook and Rassam, 2002;Ticehurst et al, 2003a;Ticehurst et al, 2003b), this study has demonstrated these approaches are not suitable for simulating water and solute movement in soils that contain vertic subsoils, water repellent topsoils or soluble silica bridging such as the texture-contrast soils investigated in this study. As Silberstein et al (1999) demonstrated in the Ucarro catchment, Western Australia, inability to simulate a reduction in subsoil hydraulic conductivity resulting from seasonal swelling of texturecontrast clay subsoils resulted in inadequate simulation of seasonal perched watertables and subsurface flow.…”
Section: Resultsmentioning
confidence: 99%
“…(), Stolte et al . () and Ticehurst et al . () have used simulation models to better predict or understand the occurrence of perched watertables and subsurface flows in texture‐contrast soils.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of theoretical considerations (Freeze and Cherry, 1979), field observations such as those in the Yizre'el Valley and our present measurements of off-plot lateral draw-down of the water table, we conclude that the primary impact of the bio-drainage is on the zones immediately beneath and just outside the plantation. Therefore, the location with the best prospects of controlling rising groundwater and the associated salinization by planting trees is in the discharge zone, and not some distance upslope in the recharge zone (Morris, 1991;Schofield and Bari, 1991;Stole et al, 1999;Benyon et al, 2001), particularly if the flows in the groundwater system are on a regional scale (Stirzaker et al, 2002). All the hills around the Yizre'el Valley are densely covered with planted forests, but this did not reduce, let alone prevent, the groundwater rise and associated widespread salinization that have plagued the valley since the mid 1980s.…”
Section: Discussionmentioning
confidence: 99%